Diapering, Diaper Technology, and Diaper Area Skin Health. (17th November 2014) - Odio, Mauricio; Thaman, Lauren
Abstract: Disposable diapers are the most common diaper care practice in Western societies today, and their use continues to increase globally. Improvements in disposable diaper technology have helped to reduce the prevalence and severity of diaper dermatitis (DD) over the course of the last few decades. This article reviews how changes in disposable diaper technology interact with the various etiological factors in DD, thus helping to improve overall diaper area skin health for children around the world.